2022
DOI: 10.5501/wjv.v11.i4.186
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic effects on the distribution of healthcare services in India: A systematic review

Abstract: BACKGROUND The coronavirus disease 2019 (COVID-19) pandemic has brought fundamental changes to our problems and priorities, especially those related to the healthcare sector. India was one of the countries severely affected by the harsh consequences of the COVID-19 pandemic. AIM To understand the challenges faced by the healthcare system during a pandemic. METHODS The literature search for this review was conducted using PubMed, EMBASE, Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
4
0
1
Order By: Relevance
“…z 2021 roku dotyczący różnych krajów zarówno Europy, jak i Ameryki, Azji i Australii [3]), albo dotyczą innych krajów (np. Indii [4]) lub wybranych obszarów świata (np. Azji Południowo-Wschodniej [5]).…”
Section: Wprowadzenie I Cel Pracyunclassified
“…z 2021 roku dotyczący różnych krajów zarówno Europy, jak i Ameryki, Azji i Australii [3]), albo dotyczą innych krajów (np. Indii [4]) lub wybranych obszarów świata (np. Azji Południowo-Wschodniej [5]).…”
Section: Wprowadzenie I Cel Pracyunclassified
“…Moreover, illiterate people could have been increasingly affected due to ignorance, which might have changed the course of the pandemic to the worst outcomes in India. Other factors that affected the healthcare system during the COVID-19 pandemic included a shortage of skilled human resources/manpower, a low doctor-to-patient ratio, and a rising burden of NCDs and infectious diseases among others [ 9 ].…”
Section: Editorialmentioning
confidence: 99%
“…We read with interest the review article by Nimavat et al [ 1 ] where they have shown healthcare difficulties impacted by the pandemic in India. We would like to emphasize the awareness, accessibilities and barriers of rehabilitation healthcare services in India and how coronavirus disease 2019 (COVID-19) pandemic has influenced it.…”
Section: To the Editormentioning
confidence: 99%